P14.50 Clinicopathological spectrum of intracranial germ cell tumors: an Indian tertiary cancer center experience. (6th September 2019) - Sahay, A; Chinnaswamy, G; Bhat, V; Patil, V; Gupta, T; Shastri, J G; Moyiadi, A; Shetty, P; Sridhar, E
Abstract: BACKGROUND: Incidence of intracranial germ cell tumors (ICGCT) in Western literature is low (0.3–0.6 %) as compared to East Asia (3–4 %), & their clinicopathological features are well documented. However, there are scant studies on ICGCT from India. MATERIAL AND METHODS: Retrospective observational study of all ICGCT histologically diagnosed in our hospital from 2007–2018. Metastasis were excluded. Clinicopathological features were retrieved from hospital's electronic medical records. RESULTS: We diagnosed 82 primary ICGCT, forming approx. 0.54 % of all primary brain tumors, & 3.5% of pediatric brain tumors. Age range: 2 months-32 yrs (Median age 14 yrs). M:F ratio: 1.82:1 (53M, 29F). Nearly 80% patients were pediatric (<18 yrs), & 8 very young ( < 3 yrs, 7M1F). Majority were suprasellar & pineal (31/82, 37% each), with one bifocal presentation. Other rarer sites: posterior fossa (4), midbrain (1), corpus callosum (1) & 11 non midline (4 thalamic, 4 frontal, 2 cerebellar, 1 CP angle). Predominant histology was germinoma (G) (51/82, 62%), while non germinomatous (NGGCT) were 31/82 (38%), of which 9 were mixed. Pure teratoma were 11 (9 immature (IT), 2 mature), & 5 pure yolk sac tumor (YST). Interestingly, all very young age group patients ( < 3 yrs), showed only NGGCT histology (5/8 IT, 3/8 pure YST). In contrast, G histology formed nearly 70% of all patients >3 yrs. Females were associated mainly with G (21/29, 72%). NGGCT were predominantly seen in males (M:F=2.9:1). Also, pure IT (9) were seen only in males. Posterior fossa tumors were all IT (4/4). Spinal tumors were NGGCT (1 mature teratoma, 1 YST). Majority of suprasellar tumors (25/31, 80.6%), other midline locations like corpus callosal, midbrain, & all thalamic tumors were G. However, pineal tumors showed equal distribution of G (15/31) & NGGCT (16/31). Spine screening was positive in 8 patients (6 G, 2 IT)- 7 on MRI and 1 only on CSF cytology. Serum tumor markers were raised in 13/54 cases- 6/34G(17.6%), vs 7/20 NGGCT (35%). CSF tumor markers were raised in 14/34-10/23 G (43.4%), vs 4/11 NGGCT (36.3%). Follow up was available for 37 patients (Duration 3 months-10 yrs, median 2 yrs). On f/u 6/15 (40%) NGGCT showed progression/death, while only 2/32 G relapsed (6.5%). Four deaths in G group were not directly attributable to the tumor. CONCLUSION: Frequency of ICGCT in our hospital similar to western data rather than Asian, albeit with less striking male preponderance. ICGCT were tumors of 2 nd decade & majority occurred in pineal/suprasellar areas. About 2/3 rd were pure G on histology, and showed good prognosis. NGGCT were common in infants, males and in posterior fossa. IT were seen exclusively in males and pure YST mainly in males. Although majority of ICGCT are in midline, rarely non midline involvement also occurs, and it's essential to exclude metastasis before considering primary ICGCT. Expectedly, NGGCT showed poorer prognosis, compared to pure germinomas.